PRINCIPAL RESEARCH ON PHYSIOLOGY AND BIOCHEMISTRY OF VEGETABLES, FRUIT AND BERRIES CROPS WITH IMPROVED ANTIOXIDANTS CONTENT - M.S. Gins; V.K. Gins; A.A. Bayikov (Овощи России, 2011)
On 25th February, 2011 the jubilee international conference "The Role of Physiology and Biochemistry for Plant Introduction and Breeding of Vegetables, Fruit and Berries Crops and Medicinal Plants» was held in All-Russian Research Institute of Vegetable Breeding and Seed Production at laboratory of plant physiology and seed research and that was dedicated to 130th anniversary of Prof. Zhegalov's birth; and 80 years since the laboratory of plant physiology and seed research was organized. The major directions of plant physiology and biochemistry research in vegetables, fruit and berries crops that were presented by scientists from the former USSR republics and far abroad were reported in this article.